PERFORMANCE CHARACTERIZATION OF A MICROWAVE TRANSISTOR - GUNES, F; GUNES, M; FIDAN, M (IEE-INST ELEC ENG, 1994)
The maximum transducer power gain G(Tmax) of a bilateral microwave transistor is analytically expressed in terms of only noise figure F, input VSWR V-i and the open-circuit parameters \z\. The analysis is based on a geometrical approach using the constant noise, input VSWR and gain circles in the source and input impedance planes keeping the solution within the physical bounds. The corresponding source Z(S) and load Z(L) terminations are also obtained analytically. Cross-relations among the possible (F, V-i, G(Tmax)) triplets have been utilised in obtaining the. performance contours of a microwave transistor at an operating frequency and bias condition. This type of representation of performance promises to be used in data sheets of microwave transistors by manufacturers in forthcoming years.
Keywords: MICROWAVE TRANSISTOR; TRANSISTOR PERFORMANCE CHARACTERIZATION; Engineering